A different view of literacy. Issue 2 (8th April 2021) - Imray, Peter; Sissons, Mike
Abstract : The Equals Formal Curriculum English Scheme of Work has been designed for that very small percentage of the school population, perhaps as low as one or two per cent, who have global learning difficulties (GLD) to such a degree that they are consistently working at levels significantly below their age‐related peers for all of their academic lives. The term GLD includes all those in England currently ascribed as having severe learning difficulties (SLD) and many if not most, currently ascribed as having moderate learning difficulties (MLD). Evidence of the difficulties faced by such pupils will become increasingly obvious beyond Year 1 at age 6, because the difficulties are global rather than specific. That is, they are likely to affect all learning, but will be particularly apparent in numeracy and literacy. This paper, the first of two, seeks to clarify why reading and writing are so extraordinarily difficult for this population and posits that the answers lie in challenging perceived wisdoms within the education system's predilections towards (i) regarding phonics as the only solution to reading difficulties (ii) persisting over time (and in the face of evidence to the contrary) with the view that children, young people and adults with GLD can make sufficient progress within phonics teaching and (iii) the use of differentiation of a standardised national curriculum model as being a sufficient answer to global learning difficulties. Clearly the main language used in England is English, but the principles and ideas outlined in this paper should apply in any language which uses a phonic structure when teaching language.